Qur'anic spiritual mindfulness: Al-Qur’an thematic interpretation - Zakiyah, Ermita (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2025)
This study aims to formulate the concept and application of spiritual mindfulness based on Qur'anic values and analyze its contribution to developing the mental and spiritual health of Muslim individuals in the contemporary era. Qur'anic mindfulness is perceived as full awareness of Allah's presence and will in every aspect of life, which is practiced through understanding and appreciating the verses of the Qur'an. This concept offers a synthesis between modern psychological principles and Islamic values, resulting in a new approach that not only emphasizes presence in the moment but also connection with God in facing the various dynamics of life. This study uses thematic interpretation analysis and empirical study methods with data analysis using PRISMA, including Identification, Screening, Eligibility, and Inclusion, to explore how this practice can strengthen emotional resilience and provide psychological calm, especially when facing anxiety and life crises. The study found that Qur'anic mindfulness is not merely a short-term psychological solution, but also forms a solid spiritual foundation, strengthens self-awareness, and supports a transcendental relationship with Allah. This practice is believed to reduce anxiety and increase resilience. Thus, the impact of Qur'anic spiritual mindfulness has the potential to become a universal and effective psychotherapeutic intervention to support mental and spiritual well-being in modern multicultural societies. Keywords: Qur’anic mindfulness, spiritual intelligence, mental health, self-awareness, thematic interpretation Copyright ©2025. The Authors. Published by Psikoislamika: Jurnal Psikologi dan Psikologi Islam. This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0